2012
DOI: 10.1177/0731684412456445
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/glass fiber/nanoclay hybrid composites: morphological, thermal, dynamic mechanical and impact behaviors

Abstract: Polypropylene/E-glass fiber/nanoclay were compounded with a twin-screw extruder and injection molded. Thermal, dynamic mechanical, and impact tests were carried out. Differential scanning calorimetry investigations showed that the incorporation of nanoclay into polypropylene/glass fiber composite shifted the melting temperature (T m ) to higher values. The degree of crystallinity (X c ) was strongly influenced by the presence of the glass fiber and nanoclay in the matrix. Dynamic mechanical analysis showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 28 publications
5
41
1
1
Order By: Relevance
“…For the samples filled with GNPs, the degree of crystallinity of the PP increased with increasing filler content, indicating the high nucleating ability of the nanoplatelets. The crystallinity of the PP-GF samples decreased, however, with increasing GF loading, suggesting that the GFs actually interrupted the linear crystallizable sequence of the macromolecular chains of polypropylene [27,28]. Finally, it was found that the samples filled with the hybrid filler also exhibited a higher degree of crystallinity than the pure matrix.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 95%
“…For the samples filled with GNPs, the degree of crystallinity of the PP increased with increasing filler content, indicating the high nucleating ability of the nanoplatelets. The crystallinity of the PP-GF samples decreased, however, with increasing GF loading, suggesting that the GFs actually interrupted the linear crystallizable sequence of the macromolecular chains of polypropylene [27,28]. Finally, it was found that the samples filled with the hybrid filler also exhibited a higher degree of crystallinity than the pure matrix.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 95%
“…For the uncompatibilised system, the XRD patterns exhibited a significant increase in interlayer d-spacing (1.25 nm after compounding). This indicates that with higher processing screw speed, the PP is able to intercalate into the NC interlayer, even with poor compatibility between PP and NC [12] . Furthermore, for compatibilised systems, XRD peaks are continually shifted to lower angles, indicating an increase in interlayer d-spacing by the diffusion of PP chains.…”
Section: X-ray Diffraction Propertiesmentioning
confidence: 99%
“…Generally, the compatibilised hybrid composites displayed improved Eʺ values throughout the experimental temperature range. The addition of 2 wt% of MAPP into PP/GF15/NC6 hybrid composite shifted the The ratio of the loss modulus to the storage modulus is measured as the damping factor or mechanical loss (tan δ) [2,12] . Since the damping peak occurred in the region of the glass transition where the material changed from a rigid to a more elastic state, it is associated with the movement of small groups and chains of molecules within the polymer structure [30] .…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%
See 2 more Smart Citations